Efektivitas Media Sosial Instagram dalam Penyebaran Informasi Covid-19 oleh Diskominfo Kota Kupang Provinsi NTT - Dudy Obed Ajinegoro; Kurniawan Kurniawan (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2023)
The spread of COVID-19 certainly has an impact on the pattern of our lives. The public is required to always maintain health to prevent the transmission of COVID-19, therefore, the communication and Information Office(Diskominfo) of Kupang City as a government agency that oversees the spread of COVID-19 information has made various efforts in the context of preventing and overcoming COVID-19 related to the dissemination of information in the form of appeals, recommendations, orders. and developments related to COVID-19. The problem of this study is to determine the level of effectiveness of the spread of COVID-19 information in Kupang City through social media, Instagram. The research conducted aims to analyze and describe the effectiveness of the use of social media Instagram by the Diskominfo of Kupang City in the dissemination of COVID-19 information as well as the factors that are obstacles and efforts to overcome obstacles to the spread of COVID-19 information and measure the level of effectiveness in the spread of COVID-19 carried out by Diskominfo Kota Kupang through Instagram as the media with the largest followers. The study used a descriptive qualitative method by looking at the pattern of community behavior through interview data in the form of questionnaires and interview data from relevant government officials as well as supporting data relating to the factors in disseminating information on COVID-19 through social media Instagram in Kupang City. Based on the results of the study, it is known that the process of disseminating information on COVID-19 carried out by the Diskominfo of Kupang City has reached an effective standard with COVID-19 cases in the city of Kupang which tend to decline and changes in people's behavior that are increasingly obedient to health protocols. The dissemination of information related to COVID-19 has been maximized and some improvements are needed so that the information dissemination process can be maximized.